2017
DOI: 10.1111/anec.12426
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of ectopic beats from 48‐hr ambulatory electrocardiography: The Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background The purpose of this study was to characterize the repeatability of ectopic beats, defined by premature atrial contractions (PACs) and premature ventricular contractions (PVCs), on ambulatory electrocardiogram (aECG) monitoring and evaluate the effect of length of aECG monitoring on the repeatability estimates. Methods This analysis includes 95 randomly selected participants from the Atherosclerosis Risk in Communities Study (ARIC; 2011–2013). The participants wore a Holter monitor for two, 48-hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Limited information is available from general population studies about the consistency of estimates of supraventricular and ventricular ectopy with extended or repeat recording. A previous analysis of data from two 48-hour Holter monitors worn an average of 38 days apart in the Atherosclerosis Risk in Communities study showed high agreement for PAC and PVC counts per hour when repeated recording periods of 3 hours were considered (ICCs 0.80 and 0.74, respectively) and even better agreement for repeated recording periods of 24 hours (ICCs 0.84 and 0.84, respectively) [11]. Our findings extend these observations to longer recording periods, demonstrating very high consistency in findings for two recording periods of an average of 12 days each (ICCs 0.88 and 0.82, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…Limited information is available from general population studies about the consistency of estimates of supraventricular and ventricular ectopy with extended or repeat recording. A previous analysis of data from two 48-hour Holter monitors worn an average of 38 days apart in the Atherosclerosis Risk in Communities study showed high agreement for PAC and PVC counts per hour when repeated recording periods of 3 hours were considered (ICCs 0.80 and 0.74, respectively) and even better agreement for repeated recording periods of 24 hours (ICCs 0.84 and 0.84, respectively) [11]. Our findings extend these observations to longer recording periods, demonstrating very high consistency in findings for two recording periods of an average of 12 days each (ICCs 0.88 and 0.82, respectively).…”
Section: Discussionmentioning
confidence: 99%
“…The European Society of Cardiology guidelines suggest that patients who have arrhythmia-related symptoms should receive a 24-h ambulatory ECG, in order to detect potential detrimental ventricular arrhythmia and conduction disorders and preventing SCD [ 6 , 7 ]. The most common finding on AECG are ectopic heart beats: premature atrial complexes (PACs) and premature ventricular complexes (PVCs) originating from the atrial and ventricular myocardium, respectively [ 8 ]. AECG allows for quantification of PACs and PVCs, respectively called “PAC or PVC burden” wherein the number of PACs or PVCs is expressed as a percentage of the total number of recorded heartbeats.…”
Section: Introductionmentioning
confidence: 99%